Development of fast and accurate algorithm to extract the five parameters of photovoltaic modules - Hisham Haider; Syafrudin Masri; Abdul-Malik H. Y. Saad; Ashraf Bani Ahmad; Tole Sutikno (Bulletin of Electrical Engineering and Informatics, 2020)
The mathematical model of a photovoltaic (PV) cell can help in analyzing the PV system performance easily. In this paper, a new algorithm is developed to determine the values of five parameters model of photovoltaic module. The proposed method which is called Extract the Five Parameters of Photovoltaic Modules (EFPPM) is used to find the optimum values of the I-V equation’s parameters that fit with I-V curve. This method could reduce the computation time of finding the values of PV model parameters. The proposed algorithm does not only reduce the computation time but it provides accurate values of PV model’s parameters, too. A comparison with conventional algorithm shows superiority of the proposed EFPPM in term of computation speed. The results show that the reduction of the computation time can reach nearly twenty one times faster. The results also clarify that the I-V and P-V curves of EFPPM are exactly the same as provided by data sheets.